A review of ventilation in adult out‐of‐hospital cardiac arrest. Issue 3 (28th April 2020) - Neth, Matthew R.; Idris, Ahamed; McMullan, Jason; Benoit, Justin L.; Daya, Mohamud R.
Abstract: Out‐of‐hospital cardiac arrest continues to be a devastating condition despite advances in resuscitation care. Ensuring effective gas exchange must be weighed against the negative impact hyperventilation can have on cardiac physiology and survival. The goals of this narrative review are to evaluate the available evidence regarding the role of ventilation in out‐of‐hospital cardiac arrest resuscitation and to provide recommendations for future directions. Ensuring successful airway patency is fundamental for effective ventilation. The airway management approach should be based on professional skill level and the situation faced by rescuers. Evidence has explored the influence of different ventilation rates, tidal volumes, and strategies during out‐of‐hospital cardiac arrest; however, other modifiable factors affecting out‐of‐hospital cardiac arrest ventilation have limited supporting data. Researchers have begun to explore the impact of ventilation in adult out‐of‐hospital cardiac arrest outcomes, further stressing its importance in cardiac arrest resuscitation management. Capnography and thoracic impedance signals are used to measure ventilation rate, although these strategies have limitations. Existing technology fails to reliably measure real‐time clinical ventilation data, thereby limiting the ability to investigate optimal ventilation management. An essential step in advancing cardiac arrest care will be to develop techniques to accurately and reliably measure ventilation parameters. These devices should allow for immediate feedback for out‐of‐hospital practitioners, in a similar way to chest compression feedback. Once developed, new strategies can be established to guide out‐of‐hospital personnel on optimal ventilation practices.